Workplace written Literacy and its effect on the curriculum - Siti Hamin Stapa,; Tg Nor Rizan Tg Maasum,; Rosniah Mustaffa,; Saadiyah Darus, (Penerbit UKM, 2008)
Fennick et al. (1993) identify employees poor writing skills on different writing requirements between school and work. The results of a research conducted by Sidy (1999) indicated that the participants could not relate what they did in freshman writing classes to the types of writing they have to do in the workplace. The objective of this paper is to discuss workplace written literacy demands and the levels of written literacy among applicants for a job at Universiti Kebangsaan Malaysia (UKM). Data was collected using interviews and a written test. The findings suggest that there exists a mismatch between written literacy demands and the levels of the applicants. Hence, there is a need to look at the present curriculum in written literacy both at secondary and tertiary levels with a view to incorporate workplace literacy components.